MODEL PENDIDIKAN AKHLAK TERINTEGRASI: STUDI KASUS PEMBENTUKAN KEPRIBADIAN MUSLIM DI PONDOK PESANTREN ANWARUSSUNNAH PETANAHAN - Muhammad Muhammad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
The purpose of this study is to analyze the implementation and effectiveness of the moral education model in shaping the Muslim character of students at the Anwarussunnah Islamic Boarding School in Petanahan. The research method employed a qualitative approach using a case study design. Data were collected through participant observation, in-depth interviews with 10 informants, and document analysis, and were subsequently analyzed thematically. The results indicate that moral education is implemented through an integrated four-pillar model: (1) exemplary leadership (qudwah hasanah), (2) habit formation (ta‘wīd), (3) structured activities with a moral focus, and (4) the integration of values into the boarding school system. This model effectively fosters religious discipline, akhlakul karimah, ukhuwah islamiyah, and self-confidence among students. The study’s conclusion emphasizes that systemic synergy among the pillars is the key to the effectiveness of the pesantren’s moral education model. This research offers practical contributions to strengthening character education based on Islamic values and theoretical implications for the development of a holistic moral education model.